Poliploidía En Moluscos De Importancia Comercial. A Review - Maldonado-Amparo, Rosalío; Verdugo, Cesar Arturo Ruiz; Ibarra, Ana María; Rueda-Puente, Edgar Omar; Del Toro Sánchez, Carmen Lizette; Félix, Francisco Rodríguez (European Scientific Journal, ESJ, 2016)
Polyploidy is a biotechnology that in the last decade had provided with an improvement method for mollusks in aquaculture. Triploids have three sets of chromosomes rather than the two carried by diploids. The third set has an effect on chromosomes synapsis, producing sterility during reproduction. That sterility is the most accepted cause for the better growth seen in triploids. Artificial induction to triploidy has some problems, which can be solved by the existence of tetraploids, which could be mated to diploids to produce biological triploids. Control strategies based on prevention of disease and methods that slow the spread of such diseases. Therefore, proper management of diseases affecting the tomato crop, knowledge and understanding of the diagnosis and its infectious cycle is vital and to establish effective control measures.However, the literature is limited when it comes to auscultating information related with the poliploidía in mollusks, it´s origin and the multiple biotechnologies that develop contemporary. This study was conducted to assess and meet the trend of existing research on polyploidy in commercially important shellfissh.